Management leadership and teaching performance in a Zepita primary educational institution - Chambilla Fernández, Bladimiro (2022)
Within the educational framework, there is the presence of the leadership that exercises the authority of the institution of Zepita during the year 2017 around the teaching performance. The central purpose of the research is to determine the level of correlation between the two variables: Leadership and teacher performance. The methodology is part of the quantitative design with a population made up of teachers appointed and hired from the institution in mention. The research technique used to collect the data corresponding to the two variables was the survey, its tool being the survey questionnaire. The results obtained are positive because they confirm the hypothesis, and there is a positive correlation between management leadership and teacher performance, since the Pearson correlation coefficient between the two variables is 0.8. what makes the decision to improve teacher performance.